A basic income for France: Ideas for a debate - Matteo Richiardi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2022)
In this note we explore the distributional effects of selected options for a Universal Basic Income (UBI) scheme in France.
Keywords: 330; Public Policy; Economics; Welfare Benefits; Taxation; Microsimulation